Obstacles to educational guidance as seen by educational counselors: a field study in Hama Governorate - ., najah satifiun (Al-Adab Journal, 2015)
The current research aims to identify the obstacles facing the work of supervisors in the Syrian Arab Republic as seen by Mentors educators. To achieve this goal , the researcher built a questionnaire consisted of ( 63 ) items distributed among five areas: the constraints of professional , technical , economic constraints and financial constraints, educational and administrative obstacles , institutional obstacles personalsocial , and after checking the veracity of the questionnaire and the expense of stability and sincerity was applied to a random sample supervisors of workers in the province of Hama amounted to (66) is directed and targeted educational , has been relying on the descriptive analytical approach in dealing with the subject of current research . Where results have shown that the constraints of work supervisors in the province of Hama fall under the five key areas in order of importance as follows : economic constraints and financial , administrative obstacles , institutional , professional and technical obstacles , obstacles educational , personal and social obstacles . The research found a set of sussgestions in order to try to repair and improve the status of educational guidance, the first stage of basic education because the success of educational guidance means the success of the educational process as a whole.